A new subspecies of Papilio saharae Oberthür, 1879 (Lepidoptera: Papilionidae) from Lampedusa, Italy - Cassar, Louis-F; Catania, Aldo; Cotton, Adam M (Zootaxa, 2023)
An investigation into the only representative of the genus Papilio on the island of Lampedusa, the largest island of the Pelagian group, was conducted as part of a broader Mediterranean-wide study on the machaon complex. Over a three-year period, adults, larvae and ova were collected for further research during field visits, while an in-house breeding programme involving wild-collected gravid females was initiated with a view to examine an adequately sized series of specimens. A total of 38 adults, including 23 male specimens, >150 ova, 233 larvae, and 220 pupae were examined. In addition to a thorough morphometric assessment, statistical tests were performed using one-way ANOVA and multivariate analysis. Results demonstrate morphological characters of P. saharae and, to a lesser degree, of P. machaon, suggesting that the taxon is plausibly the outcome of a hybrid swarm whose occurrence on the island was facilitated by Pleistocene lowstands (when the island was physically connected with the north African continental landmass, the taxon’s centre of origin). Based on results, involving all four stages of metamorphosis, it is proposed to ‘anchor’ the taxon to Papilio saharae Oberthür, 1879 and assign it subspecific status, aferpilaggi ssp. nov.